Capecitabine Compared with Capecitabine Plus Oxaliplatin Chemoradiotherapy - Nichols, Emma Hitt (MD Conference Express, 2014)
Preliminary findings demonstrate that patients with rectal cancer receiving radiotherapy with a combination of capecitabine and oxaliplatin have better local regional control compared with those receiving capecitabine plus radiotherapy. This article presents interim data from the ongoing phase 3 open-label Adjuvant Treatment of Concurrent R and CAPOX or Capecitabine Alone for Stage II and III Rectal Cancer trial [NCT00714077].